The Applicability Of Force Majeure Clause During The Covid-19 Pandemic In Indonesia And France - Kang, Cindy; Quentin, Pinsolle-Dubourg; Gia Phuc, Dao; Tan, David (Jurnal Komunikasi Hukum, 2021)
The Covid-19 pandemic that has occurred almost all over the world has had a very significant impact on various aspects. In this regard, the pandemic has directly or indirectly affected international trade. International business contracts are one of the essential elements in carrying out an international trade. The covid-19 pandemic that has occurred has resulted in implications and disruption to the ongoing contracts carried out on international scale. The current pandemic has raised a question, whether if the covid-19 pandemic can be classified as a force majeure circumstances or not. Reflecting on these problems, this study will examine the rules and regulations of force majeure from the legal perspective of Indonesia and France as countries that have adopted the civil law legal system. In addition, this study also discusses about the impacts of the covid-19 pandemic on international trade contracts. This study uses normative legal research methods, namely methods based on written regulations and literature that examines aspects of theories, structure, and legal explanations related to the material in this research. The approach used in writing this journal is a comparative approach which is to compare the legal regulations in Indonesia andÂ France. From the second data sources obtained, it is found that there are some differences between Indonesian and French laws regarding force majeure. The Indonesian civil code does not explicitly mention force majeure, but calls it as a state of coercion. Meanwhile, civil law in France clearly mentions force majeure in the France Civil Code. Related to the covid-19 pandemic which is classified as a force majeure condition, the parties bound in international business contracts can renegotiate the contracts they made.